Part A:
5+x-12=x-7
Combine like terms:
x-7=x-7
Add 7 to both sides:
x=0
Therefore, the solution to the equation 5+x-12=x-7 is x=0.
Part B:
Substitute x=-4 into the equation:
5+(-4)-12=(-4)-7
-11=-11
The equation is true for x=-4.
Substitute x=0 into the equation:
5+0-12=0-7
-7=-7
The equation is true for x=0.
Substitute x=5 into the equation:
5+5-12=5-7
-2=-2
The equation is true for x=5.
Therefore, the solution x=0 is verified by substituting x=-4, 0, and 5 into the equation.
the equation 5+x-12=x-7:Part A. Solve the equation 5+x-12=x-7. In your final answer, be sure to state the solution and include all of your work.
Part B. Use the values x=-4,0,5 to verify your solution to the equation 5+x-12=x-7In your final answer, include all of your calculations.
2 answers
solution is bogus
adding 7 to both sides produces
x = x
which is true for any value of x.
adding 7 to both sides produces
x = x
which is true for any value of x.